Association Between Neopterin Levels and Outcome in 30 Day HIV/AIDS Naive Patients - Juanita, Lydia; Hadi, Usman; Arfijanto, Vitanata (Faculty of Medicine, Universitas Airlangga, Surabaya, Indonesia, 2019)
Introduction: HIV/AIDS is still a major problem throughout the world even in Indonesia. Some markers can provide information regarding the description of immune activity in HIV/AIDS. Neopterin produced by macrophages as a catabolic result of Guanosine Triphosphate (GTP) is one of them. Neopterin has been widely studied as a prognostic indicator of the course in HIV/AIDS. Until now there have been no studies examine the association between neopterin levels and outcomes in 30 days of HIV/AIDS patients.Methods: A prospective longitudinal analytic study involved 56 samples of HIV/AIDS naive patients from January to April 2019. Serum neopterin levels were measured by the Enzyme Linked Immunosorbent Assay (ELISA) method. Outcome is a living condition or death within the first 30 days of the patient being treated. Discriminant function analysis was used to determine the association between variable and controlling confounding factors using the